Effects of Magnetic Field Exposure on Biosynthetic Reaction of Gold Nanoparticles (AuNP) Using Sambiloto Leaf Extract (Andrographis paniculata ness) - Imas, Maria Yulni; Wulandari, Ratih; Rupiasih, Ni Nyoman; Supardi, I Wayan (BULETIN FISIKA, 2020)
Research has been conducted to determine the effect of magnetic field exposure on the biosynthesis reaction of gold nanoparticles (AuNP) using Sambiloto leaf extract (Andrographis paniculata ness). The observations were made in two stages, namely optimization and synthesis rate. The optimization stage is carried out in a variation of the synthesis ratio (AuCl 3 solution (in ?l): Sambiloto leaf extract (in ml)) which are 2:10, 5:10, 10:10, 15:10, 20:10, 30:10 and 40:10. The results obtained from the optimization stage are used at the stage of determining the rate of synthesis reaction and then used to study the effect of magnetic field exposure on the rate of the AuNP synthesis reaction. The magnitude of the magnetic field used is 1.5 mT and exposure time of 12 hours. The synthesis results were characterized using UV-Vis spectrophotometer with the result that the absorbance value is a function of the wavelength of Surface Plasmon Resonance (SPR). The optimization phase was obtained that the synthesis volume ratio of 30 ?l: 10 ml gave the greatest absorbance value for the synthesis time of ± 1 hour. The reaction rate stage was obtained that the optimum time for AuNP synthesis was 1 hour both without and with the effect of magnetic field exposure, with the characteristic wavelength of the SPR and its absorbance value without the field of 535.5 nm, 0.938 a.u. and with a field of 526.0 nm, 0.880 a.u.